Forage yield and morphogenetic and structural characteristics of Megathyrsus maximus cv. Zuri under defoliation levels - Costa, Newton; Costa, Newton de Lucena; Jank , Liana; Magalhães , João Avelar; Rodrigues , Antônio Neri Azevedo; Bendahan, Amaury Burlamaqui; Fogaça , Fabíola Helena dos Santos; Santos, Francisco José de Seixas (Pubvet, 2019)
The effects of defoliation level (20, 30, 40 and 50 cm above soil level) on green dry matter (GDM) yield and morphogenetic and structural characteristics of Megathyrsus maximus cv. Zuri were evaluated under field conditions in Roraima´s savannas. The effects of defoliation level on the GDM yields, leaf area index and leaf elongation rates was adjusted to the quadratic regression model and maximum values recorded with cutting at 42.7; 42.2 and 41.1 cm above soil level, respectively. The population tiller density, number of leaves plant-1 and leaf appearance rate was inversely proportional to the level of defoliation, while the opposite occurred for to medium blade length and leaf senescence rate. Apical meristem removing percentage was higher with increasing defoliation level. Aftermath regrowth showed close negative correlation with defoliation level. Pastures of M. maximus cv. Zuri managed under 40 cm residue provides higher forage productivity, larger efficiency of forage utilization, greater tissue renewal and canopy structure more favorable to grazing.
Keywords: Green dry matter; leaves; tillering; senescence